MANF Produced by MRL Mouse-Derived Mesenchymal Stem Cells Is Pro-regenerative and Protects From Osteoarthritis - Tejedor, Gautier; Luz-Crawford, Patricia; Barthelaix, Audrey; Toupet, Karine; Roudières, Sébastien; Autelitano, François; Jorgensen, Christian; Djouad, Farida (Frontiers in Cell and Developmental Biology, 2021)
The super healer Murphy Roths Large (MRL) mouse represents the “holy grail” of mammalian regenerative model to decipher the key mechanisms that underlies regeneration in mammals. At a time when mesenchymal stem cell (MSC)-based therapy represents the most promising approach to treat degenerative diseases such as osteoarthritis (OA), identification of key factors responsible for the regenerative potential of MSC derived from MRL mouse would be a major step forward for regenerative medicine. In the present study, we assessed and compared MSC derived from MRL (MRL MSC) and C57BL/6 (BL6 MSC) mice. First, we compare the phenotype and the differentiation potential of MRL and BL6 MSC and did not observe any difference. Then, we evaluated the proliferation and migration potential of the cells and found that while MRL MSC proliferate at a slower rate than BL6 MSC, they migrate at a significantly higher rate. This higher migration potential is mediated, in part, by MRL MSC-secreted products since MRL MSC conditioned medium that contains a complex of released factors significantly increased the migration potential of BL6 MSC. A comparative analysis of the secretome by quantitative shotgun proteomics and Western blotting revealed that MRL MSC produce and release higher levels of mesencephalic astrocyte-derived neurotrophic factor (MANF) as compared to MSC derived from BL6, BALB/c, DBA1 mice. MANF knockdown in MRL MSC using a specific small interfering RNA (siRNA) reduced both MRL MSC migration potential in scratch wound assay and their regenerative potential in the ear punch model in BL6 mice. Finally, injection of MRL MSC silenced for MANF did not protect mice from OA development. In conclusion, our results evidence that the enhanced regenerative potential and protection from OA of MRL mice might be, in part, attributed to their MSC, an effective reservoir of MANF.